Pengayaan Manajemen Pada Optik Jaya Padang - Rina Novalinda (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
Based on the implementation of community service activities, it is known that in general the counseling participants do not understand in depth about the functions and skills needed by management. This problem is mainly because Optik Jaya Padang has never attended counseling on this matter, so they experience skin problems in implementing it in the cooperative's internal environment. From the results obtained, it is suggested that a preliminary survey be conducted regarding the target audience and the topic to be given. It is hoped that this activity will be right on target and effective for participants. Counseling to the management of Optik Jaya Padang should be carried out routinely and continuously to enrich the understanding and application of management functions and skills at every level of management at the Optics.